HEALTH HAZARDS DUE TO SHORTAGE OF WATER DURING SUMMER SEASON IN PORT SUDAN TOWN DECEMBER 2006-DECEMBER 2008. - S.M, Ahmed; F.A. Elhassan, Hassan; B.M, Ali (Gezira Journal of Health Sciences; Vol 6 No 2 (2010), 2010)
Portsudan, the harbour of Sudan if facing a serious problem concerning shortage of water supply . The Town is supplying ships with fresh water against the need of portsudan town . It has been noticed that the peek of shortage of water supply happens in summer season (66%) also the big need to water in summer leads certain practices which affected the quality of water in the town , these problem distribution of water through tankers and donkey cars, improper pipe lime distribution , as well as different ways of storing water in houses . Bacteriological and chemical tests conducted resulted in pollution with E. coli in shallow wells in Arbaat and open takers in the town as well as during the method of water transpiration and storing in houses . Diseases associated with water shortage in summer showed an abnormal high level on gastroetrits, diaroahea, hipititis , disentaries poor personal high and even food poisoning . The study recommended that still there in great hope for nile water to reach portsudan . However bottled fresh water from North Sudan with subsidized price to fill the gab of shortage of drinking water is carried out In town .